Implementasi Media Pembelajaran Interaktif Mata Kuliah Pengantar Multimedia Menggunakan App Inventor Berbasis Android - Basrul Basrul; Hazrullah Hazrullah; Nora Azlina (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
App Inventor 2 was used to construct interactive media for multimedia introductory classes. However, the study was conducted by employing the Multimedia Development Life Cycle (MDLC) technique. The Concept, design, material collection, assembling, testing, and distribution are the six stages that run up the whole method. The results showed that the validation of media experts was in range 79% and categorized as feasible. While the validation results of material experts are 73% and categorized as feasible. The results of the test on users obtained 84% and stated that the interactive media is acceptable and feasible to be applied as teaching and learning facilities in terms of the introductory multimedia courses.